Diplomacia imperial: a política externa brasileira nas viagens de Dom Pedro II (1871-1888) - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This monograph analyzes Brazilian foreign policy during the Second Reign, highlighting Dom Pedro II's international travels as instruments of diplomacy and projection of prestige for the Brazilian Empire between 1871 and 1888. Using a constructivist approa ch and the concept of prestige politics, we investigate how the emperor used his image and his encounters with foreign leaders and intellectuals to strengthen Brazil’s position in the international arena and promote a modern and progressive national identi ty through conferences, arbitrations, and congresses. The study also examines the influence of these travels in building a favorable image of Brazil among European powers and the United States, aiming to elevate the country’s status as a regional power and to overcome its image as a peripheral, slave holding, and little known nation in the international sphere. To achieve this, we conducted a qualitative analysis of historical, documentary, and bibliographic sources including letters, diaries, and documents exploring the impact of the emperor’s presence at international events and meetings during his travels in consolidating an autonomous and prestígio us foreign policy. The research confirms that Dom Pedro II’s international travels played a role in strengthening Brazil’s prestige on the global stage, projecting the emperor as an enlightened and progressive monarch, and forming part of a larger prestige p olicy that was later leveraged, in its overall benefits, by the republic through the work of Barão do Rio Branco.
Imperial diplomacy: Brazilian foreign policy during the travels of Dom Pedro II (1871-1888)
Keywords: Política externa brasileira; Dom Pedro II; Diplomacia imperial; Relações internacionais; Brasil império; Século XIX; Construtivismo; Brazilian foreign policy; Imperial diplomacy; International relations; Empire of Brazil; 19th Century; Constructivism; CIENCIAS SOCIAIS APLICADAS